The Impact of Using Bamboo Activated Carbon as Counter Electrode and Dye from Suji Leaf toward the Efficiency of Dye Sensitized Solar Cells - Ismail, Muhammad Fakhri; Taqwa, Ahmad; Kusumanto, R.D (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Dye-sensitized solar cells (DSSCs) have attracted great interest due to their ability to convert solar energy into electricity cost-effectively and efficiently. This study aims to create Dye-Sensitized Solar Cells (DSSCs) by utilizing bamboo activated carbon as the counter electrode and natural dyes derived from suji leaves as photosensitizers. Bamboo activated carbon was chosen because of its sustainable nature, large surface area, and excellent conductivity. Likewise, suji leaf dye was chosen because of its capacity to absorb various wavelengths of light. These materials were analyzed using UV-Vis spectroscopy, XRD, and SEM to determine their structure and characteristics. The results of the DSSC efficiency showed that using bamboo activated carbon as the counter electrode produced the highest energy conversion efficiency of 0.0000896%, surpassing the achievement of carbon black electrodes, which only reached 0.0000505%.